Magneto–Thermoelectric Effects in Compositional Superlattice in the Presence of Electromagnetic Wave - Thu Hang, Dao; Thi Hoa, Nguyen; Thi Thanh Nhan, Nguyen; Quang Bau, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 35 No 3DO - 10.25073/2588-1124/vnumap.4336, 2019)
This paper surveys the Ettingshausen coefficient (EC) in the compositional semiconductor superlattice (CSSL) under the influence of electromagnetic wave (EMW) by using the quantum kinetic equation for electrons. The analytical expressions of the Ettingshausen coefficient are numerically calculated for the GaAs/AlGaAs compositional semiconductor superlattice. The survey results show that the appearance of EMW changed the EC’s value and the EC decreased nonlinearly when the temperature increased. The study of the dependence of EC on the magnetic field discovers that the superlattice period strongly affects the quantum magneto- thermoelectric effect. Accordingly, when the superlattice period is small, the quantum EC resonance peaks appear and when the superlattice period is large, resonance peaks disappear. The quantum theory of the magneto-thermoelectric effect was studied from low temperature to high temperature. The result overcomes the limitations of the Boltzmann kinetic equation which was studied at high temperatures. The results are new and can serve as a basis for further development of the theory of magneto-thermoelectric effects in low-dimensional semiconductor systems.